Morfometry Diversity of Uceng Fish (Nemacheilus fasciatus) With Truss Method In Downstream of Yeh Sungi River - Gede Dabdab Suriadi; Sang Ayu Made Putri Suryani; I Wayan Arya (Warmadewa University Press, 2019)
This study aims to determine the morphometric diversity of uceng fish that live in the downstream of the yeh sungi river and the environmental influence on the morphometry of the uceng fish that lives in the lower reaches of the yeh sungi river. This research was carried out in the Lower Sections of the Yeh Sungi River, Kediri District, Tabanan Regency, Bali Province. This research began on January 3 to April 17, 2019. The research method used was descriptive observation method by holding a series of sampling objects under study or data objects directly at the research location, in this study the intended data objects were uceng fish and types other fish caught as well as water quality. Uceng fish was measured by the truss method and the characters observed were 13 characters, namely A1, A2, A3, B1, B2, B3, B4, B5, C1, C2, C3, C4, and C5. The results of the study showed that the morphometry characters of Uceng fish (Nemacheilus fasciatus) that live in the lower reaches of the Yeh Sungi river were 13 characters observed at the Stasion I, Station II, and Station III, from the characters observed 5 characters had similarities (38.46% ) that is on the characters A1, B1, B2, B4, and B5, while 8 characters have differences (61.54%), namely the characters A2, A3, B3, C1, C2, C3, C4, and C5. The high difference shows that uceng fish in the downstream of the Yeh Sungi river are resistant to environmental changes, other fish caught include broom fish, beboso fish, wader fish, catfish, gouramy fish, klepek batu, and cork fish and range water quality parameters during the study were temperature 25 0C, pH 5-7, DO 6 ppm, NO3 - 0.5 mg / l, and KH 6-10 dH.